2017
DOI: 10.2119/molmed.2017.00091
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Acetylcholine Receptor-Mediated Protection of the Rat Heart Exposed to Ischemia Reperfusion

Abstract: Reperfusion injury following acute myocardial infarction is associated with significant morbidity. Activation of neuronal or non-neuronal cholinergic pathways in the heart has been shown to reduce ischemic injury, and this effect has been attributed primarily to muscarinic acetylcholine receptors. In contrast, the role of nicotinic receptors, specifically α-7 subtype (α7nAChR), in the myocardium remains unknown, which offers an opportunity to potentially repurpose several agonists/modulators that are currently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…The growing insight into the inflammatory reflex and the receptor mechanisms mediating efferent vagus nerve anti-inflammatory output prompted new clinicallyoriented research. The anti-inflammatory and diseasealleviating effects of many α7nAChR agonists, including nicotine, GTS-21, choline, and PNU-282987 have been demonstrated in preclinical settings of sepsis, postoperative neuroinflammation, ischemia-reperfusion injury, obesity and type 2 diabetes, and other disorders (Parrish et al, 2008;Pavlov et al, 2007;Chatterjee et al, 2017;Mavropoulos et al, 2017;Terrando et al, 2011;Wang et al, 2011;Li et al, 2013;Yeboah et al, 2008;Hoover, 2017;Terrando & Pavlov, 2018) (Fig. 2).…”
Section: The Collateral Scientific and Therapeutic Benefitmentioning
confidence: 99%
“…The growing insight into the inflammatory reflex and the receptor mechanisms mediating efferent vagus nerve anti-inflammatory output prompted new clinicallyoriented research. The anti-inflammatory and diseasealleviating effects of many α7nAChR agonists, including nicotine, GTS-21, choline, and PNU-282987 have been demonstrated in preclinical settings of sepsis, postoperative neuroinflammation, ischemia-reperfusion injury, obesity and type 2 diabetes, and other disorders (Parrish et al, 2008;Pavlov et al, 2007;Chatterjee et al, 2017;Mavropoulos et al, 2017;Terrando et al, 2011;Wang et al, 2011;Li et al, 2013;Yeboah et al, 2008;Hoover, 2017;Terrando & Pavlov, 2018) (Fig. 2).…”
Section: The Collateral Scientific and Therapeutic Benefitmentioning
confidence: 99%
“…82,83 Potential mechanisms for the antioxidative effects of AChE inhibitors are summarized and illustrated in both Figures 2 and 3. proteins.…”
Section: Of 24mentioning
confidence: 99%
“…76,78,82,132 As regards device therapy, VNS has been shown previously to reduce the infarct size and improve cardiac function in various animal models with cardiac I/R injury. To be specific, it has been shown that ACh, an mAChR agonist and an nAChR agonist provided cardioprotective effects in cardiac I/R injury in both in vivo and in vitro studies.…”
Section: Inhibitors Following Cardiac I/r Injury: Reports From In Vivmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a recent study reported that administration of GTS21, a selective α7nAChR agonist, significantly reduced the infarct size and improved left ventricular developed pressure (LVDP) and ±dP/dt compared with the control. The beneficial effects of GTS21 were blocked when co-administered with MLA, suggesting that GTS21 treatment decreased the infarct size and improved cardiac contractile function through the activation of α7nAChR [ 55 ]. In addition, Zhang et al have also demonstrated that the infarct size in mice hearts pretreated with electroacupuncture at the Neiguan acupoint (PC6) was significantly reduced compared with the control [ 8 ].…”
Section: The Effects Of α7 Nicotinic Acetylcholine Receptor (α7nacmentioning
confidence: 99%